三发市华人冬至节传统习俗概况 - Candy Candy; Shiela Shiela (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2024)
The title of this study is “Overview of Traditional Customs of Chinese Winter Solstice Festival in Sambas City”. The winter solstice is a very important solar term in the lunar calendar, it is the 22nd of the 24 solar terms. The winter solstice is also a traditional festival. The Winter Solstice is generally celebrated on December 21st or 22nd of the lunar calendar. The winter solstice was once called “eating glunious rice balls” by Chinese Indonesians. The purpose of the research is to understand the customs and significance of the Sambas city Winter Solstice Festival and the differences between Sambas and Chinese Winter Solstice Festivals. The author chooses Sambas Chinese as the research object. The data collection method used in this article is interviews. It can be seen from the interview results that the Sambas Chinese still celebrate the Winter Solstice Festival, but many people do not understand the meaning, significance and customs of the Winter Solstice Festival. With the development of the times, many traditional customs have gradually changed, and some customs have even slowy disappeared.